2020
DOI: 10.1097/bpo.0000000000001703
|View full text |Cite
|
Sign up to set email alerts
|

The Association of α Angle on Disease Severity in Adolescent Femoroacetabular Impingement

Abstract: Background: Femoroacetabular Impingement (FAI) is a common cause of hip pain in adolescent patients. Clinical exam and radiographic markers, such as α angle and lateral center edge angle (LCEA), are commonly used to aid in the diagnosis of this condition. The purpose of this study was to correlate preoperative α angle and LCEA with preoperative symptoms, intraoperative findings, and preoperative and postoperative patient reported outcomes (PROs) in the adolescent patient. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 35 publications
0
4
0
2
Order By: Relevance
“…Bei Adoleszenten mit FAI sind Knorpelschäden mit 88,4 % sehr häufig und korrelieren in ihrem Ausmaß mit dem Alphawinkel [ 33 ]. Dabei weisen Patienten mit Post-ECF-Slip Deformitäten im Vergleich zum primären Cam-FAI häufig einen höheren Alphawinkel und ausgedehntere Knorpelschäden auf; zudem sind die Patienten im Schnitt jünger [ 34 ].…”
Section: Radiologische Befunde Beim Faisunclassified
“…Bei Adoleszenten mit FAI sind Knorpelschäden mit 88,4 % sehr häufig und korrelieren in ihrem Ausmaß mit dem Alphawinkel [ 33 ]. Dabei weisen Patienten mit Post-ECF-Slip Deformitäten im Vergleich zum primären Cam-FAI häufig einen höheren Alphawinkel und ausgedehntere Knorpelschäden auf; zudem sind die Patienten im Schnitt jünger [ 34 ].…”
Section: Radiologische Befunde Beim Faisunclassified
“…15,[18][19][20][21][22] Seven additional studies presenting associations between LCEA and PRO measures were identified but provided insufficient data to be included in a meta-analysis. [23][24][25][26][27][28][29] All associations for which there was insufficient data to perform meta-analysis are listed in Supplemental Table 4 (http://links.lww.com/JAAOS/A849). These studies were excluded as, for each PRO, there were fewer than the minimum three studies required for quantitative synthesis reporting data in the same format-such as odds ratios or mean 6 SD-thus prohibiting meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…Likewise, Youngman et al found that increased alpha angle was significantly correlated with increased length of tear and severity of labral disease among adolescent patients with FAI. 35 In contrast to imaging for FAI, MRI and MRA are the preferred modalities for imaging of labral tears due to their superior visualization of soft-tissue structures and lesions compared with X-rays. While MRA has been shown to have higher sensitivity to labral tears than MRI, its invasive nature, higher learning curve, and use of radiation are major drawbacks.…”
Section: Physical Examination and Imaging Of Fai And Associated Labra...mentioning
confidence: 99%